Pemanfaatan limbah kelapa sawit untuk budidaya jamur merang dalam upaya perbaikan ekonomi desa: Pengabdian kepada masyarakat di Desa Kampung Baru, Kabupaten Pelalawan - Djaimi Bakce; Almasdi Syahza; Syaiful Bahri; Mitri Irianti; RM Riadi; Brilliant Asmit (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2019)
There is oil palm waste in the form of Oil Palm Empty Bunches (TKKS) in the Village of Kampung Baru, Subdistrict of Ukui, Pelalawan Regency. TKKS can be used as a medium for straw mushroom cultivation. To utilize this potential, the team provided the training and assistance in developing mushrooms product and its institutional strengthening to the community groups and local economical institutions. The team implement the activities by conducting community assistance to 20 village people. Other than that, the team gave the marketing knowledge of the mushroom product, so that it could increase the community income and economy. The activities located in the biogas plant development area. The result is participants have been able to cultivate mushroom from the process of setting the medium to harvesting. This activity has not reached the stage of harvest calculation and marketing yet. But the participants have got a mushroom products estimation that in the 144 m2 harvested area produces 34.56 kg of mushroom is per day.